Pretensive Shared Reality: From Childhood Pretense to Adult Imaginative Play - Kapitany, Rohan; Hampejs, Tomas; Goldstein, Thalia R. (Frontiers in Psychology, 2022)
Imaginative pretend play is often thought of as the domain of young children, yet adults regularly engage in elaborated, fantastical, social-mediated pretend play. We describe imaginative play in adults via the term “pretensive shared reality;” Shared Pretensive Reality describes the ability of a group of individuals to employ a range of higher-order cognitive functions to explicitly and implicitly share representations of a bounded fictional reality in predictable and coherent ways, such that this constructed reality may be explored and invented/embellished with shared intentionality in an ad hoc manner. Pretensive Shared Reality facilitates multiple individual and social outcomes, including generating personal and group-level enjoyment or mirth, the creation or maintenance of social groups, or the safe exploration of individual self-concepts (such as alternative expression of a players sexual or gender identity). Importantly, Pretensive Shared Reality (both within the specific context of table-top role-playing games, and other instances) are primarily co-operative and co-creative. We draw on multiple examples, and focus on Table-Top Role Playing games (TTRPG) – and specifically, the most popular and enduring table-top role-playing games, Dungeons & Dragons (D&D) – as a primary example of such play. Our conception of “pretensive shared reality” links the widespread existence and forms of adult imaginative play to childhood pretense, places it within a developmental and evolutionary context, and argues that pretensive shared realities – which underpin many forms of imaginative culture – are an important topic of study unto themselves, and may be utilized to provide methodological insight into a variety of psychological domains.